2016
DOI: 10.3390/soc6020015
|View full text |Cite
|
Sign up to set email alerts
|

Employment, Disabled People and Robots: What Is the Narrative in the Academic Literature and Canadian Newspapers?

Abstract: Abstract:The impact of robots on employment is discussed extensively, for example, within the academic literature and the public domain. Disabled people are known to have problems obtaining employment. The purpose of this study was to analyze how robots were engaged with in relation to the employment situation of disabled people within the academic literature present in the academic databases EBSCO All-an umbrella database that consists of over 70 other databases, Scopus, Science Direct and Web of Science and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 88 publications
0
23
0
Order By: Relevance
“…If this is the case, the question is, why is the situation so different if disabled people are covered? This discrepancy of tone of coverage based on whether one covers disabled people or non-disabled people is also evident in the robotics coverage (academic articles, newspapers) [182], and as such, our findings suggest a broader systemic problem.…”
Section: Conclusion and Future Researchmentioning
confidence: 56%
See 1 more Smart Citation
“…If this is the case, the question is, why is the situation so different if disabled people are covered? This discrepancy of tone of coverage based on whether one covers disabled people or non-disabled people is also evident in the robotics coverage (academic articles, newspapers) [182], and as such, our findings suggest a broader systemic problem.…”
Section: Conclusion and Future Researchmentioning
confidence: 56%
“…Such a hierarchy is not surprising. A recent study looking at the coverage of robotics in academic literature and newspapers made the point that many discussions exist surrounding the negative impact of robotics on the employment situation of non-disabled people, and the study also revealed that coverage of the impacts of robotics on the employment situation of disabled people was highly techno-optimistic [182].…”
Section: The Issue Of Techno-optimismmentioning
confidence: 99%
“…STEM advancements, such as the development of assistive technologies, impact disabled people in positive ways but also in negative ways. For example, there is currently a debate around precision genetic engineering [155] and the danger of automatization and robotics on employment of disabled people [156].…”
Section: Research On Disability Contributes To Stem and Science Educamentioning
confidence: 99%
“…The notion of a robot co-worker, at least in information-rich occupations, such as library work, appears to be gathering interest (Sanborn, 2015). For people with disabilities, a recent review article found generally positive anticipation of service and social robots, although accessibility (affordability and design) as well as labor competition were raised as concerns (Wolbring, 2016).…”
Section: Capability Building Technologiesmentioning
confidence: 99%